Calculation procedure for determining wind action from vortex-induced vibration with verification of fatigue strength of steel structures - Marina Rakočević; Svetislav Popović (Građevinar, 2018)
An applicable calculation procedure, implemented with an object-oriented software that calculates amplitudes of oscillation due to vortex shedding, is presented in this paper using a stadium lighting pole as an example. The fatigue strength of material is proven, for the defined S-N curves, according to the nominal stress method. Available Eurocode-based calculation methods are also analysed and their advantages and disadvantages are presented.